A Qualitative Study on Extracurricular-Based Islamic Education Learning Methods for Qur’anic Reading and Writing at SMP Negeri 2 Lasem - Laila Jumanul Wad'iyyah; Mohammad Zakki Azani (FKIP - Universitas Riau, 2026)
Qur’anic reading and writing skills remain a challenge for junior secondary school students with diverse religious backgrounds. This study examines the implementation of extracurricular-based Islamic Religious Education learning methods for Qur’anic reading and writing at SMP Negeri 2 Lasem, a public junior high school in Central Java, Indonesia. The study aims to identify the learning methods applied and their contribution to improving students’ Qur’anic literacy skills. A descriptive qualitative approach was employed through classroom observations, interviews with Islamic Religious Education teachers, extracurricular instructors, and seventh-grade students, as well as documentation analysis. The findings show that Qur’anic Reading and Writing extracurricular activities function as supportive learning spaces beyond formal classroom instruction. Lecture methods introduce basic tajwid and letter articulation, while discussion and question-and-answer methods facilitate interactive correction of reading errors. Guided practice emerged as the most effective approach for improving reading accuracy and fluency. Despite challenges such as limited time, varied student abilities, and inconsistent motivation, the integrated use of these methods contributed to improvements in students’ Qur’anic reading competence and religious character development. The study concludes that extracurricular-based Islamic Religious Education learning offers a practical model for enhancing Qur’anic literacy in public secondary schools.